Dietary-phytochemical mediated reversion of cancer-specific splicing inhibits Warburg effect in head and neck cancer - Sandhya Yadav; Somnath D. Bhagat; Amit Gupta; Atul Samaiya; Aasheesh Srivastava; Sanjeev Shukla (BMC Cancer, 2019)
Abstract Background The deregulated alternative splicing of key glycolytic enzyme, Pyruvate Kinase muscle isoenzyme (PKM) is implicated in metabolic adaptation of cancer cells. The splicing switch from normal PKM1 to cancer-specific PKM2 isoform allows the cancer cells to meet their energy and biosynthetic demands, thereby facilitating the cancer cells growth. We have investigated the largely unexplored epigenetic mechanism of PKM splicing switch in head and neck cancer (HNC) cells. Considering the reversible nature of epigenetic marks, we have also examined the utility of dietary-phytochemical in reverting the splicing switch from PKM2 to PKM1 isoform and thereby inhibition of HNC tumorigenesis. Methods We present HNC-patients samples, showing the splicing-switch from PKM1-isoform to PKM2-isoform analyzed via immunoblotting and qRT-PCR. We performed methylated-DNA-immunoprecipitation to examine the DNA methylation level and chromatin-immunoprecipitation to assess the BORIS (Brother of Regulator of Imprinted Sites) recruitment and polII enrichment. The effect of dietary-phytochemical on the activity of denovo-DNA-methyltransferase-3b (DNMT3B) was detected by DNA-methyltransferase-activity assay. We also analyzed the Warburg effect and growth inhibition using lactate, glucose uptake assay, invasion assay, cell proliferation, and apoptosis assay. The global change in transcriptome upon dietary-phytochemical treatment was assayed using Human Transcriptome Array 2.0 (HTA2.0). Results Here, we report the role of DNA-methylation mediated recruitment of the BORIS at exon-10 of PKM-gene regulating the alternative-splicing to generate the PKM2-splice-isoform in HNC. Notably, the reversal of Warburg effect was achieved by employing a dietary-phytochemical, which inhibits the DNMT3B, resulting in the reduced DNA-methylation at exon-10 and hence, PKM-splicing switch from cancer-specific PKM2 to normal PKM1. Global-transcriptome-analysis of dietary-phytochemical-treated cells revealed its effect on alternative splicing of various genes involved in HNC. Conclusion This study identifies the epigenetic mechanism of PKM-splicing switch in HNC and reports the role of dietary-phytochemical in reverting the splicing switch from cancer-specific PKM2 to normal PKM1-isoform and hence the reduced Warburg effect and growth inhibition of HNC. We envisage that this approach can provide an effective way to modulate cancer-specific-splicing and thereby aid in the treatment of HNC.